Highly Efficient Nanosecond 1.7 μm Fiber Gas Raman Laser by H2-Filled Hollow-Core Photonic Crystal Fibers - Hao Li; Wenxi Pei; Wei Huang; Meng Wang; Zefeng Wang (Crystals, 2020)
We report here a high-power, highly efficient, wavelength-tunable nanosecond pulsed 1.7 μm fiber laser based on hydrogen-filled hollow-core photonic crystal fibers (HC-PCFs) by rotational stimulated Raman scattering. When a 9-meter-long HC-PCF filled with 30 bar hydrogen is pumped by a homemade tunable 1.5 μm pulsed fiber amplifier, the maximum average Stokes power of 3.3 W at 1705 nm is obtained with a slope efficiency of 84%, and the slope efficiency achieves the highest recorded value for 1.7 μm pulsed fiber lasers. When the pump pulse repetition frequency is 1.3 MHz with a pulse width of approximately 15 ns, the average output power is higher than 3 W over the whole wavelength tunable range from 1693 nm to 1705 nm, and the slope efficiency is higher than 80%. A steady-state theoretical model is used to achieve the maximum Stokes power in hydrogen-filled HC-PCFs, and the simulation results accord well with the experiments. This work presents a new opportunity for highly efficient tunable pulsed fiber lasers at the 1.7 μm band.